The Sculpted Image : a panorama of contemporary Indian Sculpture : Bombay Arts Festival '87 - Bombay Arts Festival Bombay 1987 (Bombay : Bombay Arts Festival, 1987)
Davierwalla, Adi ; Gujral, Satish ; Mukherjee, Meera ; Nayar, Ved ; Shah, Himmat ; Patel, Jagji ; Kaneria, Raghav ; Mukherjee, Mrinalini ; Patel, Trupti ; Pushpamala N. ; etc.
The Sculpted Image : a panorama of contemporary Indian Sculpture : Bombay Arts Festival '87, Terrace of Nehru Centre, Bombay, 15th to 30th November 1987
boek
Keywords: Pochkhanawala, Pillo